Intervenções urbanas e transformação espacial na região Mendanha de Goiânia - Souza, Dayane Lino de (2015)
The allocation of value in use and especially of the soil exchange value is consolidated, and this makes the earth one of the most profitable and efficient sources of income of the city, through the action of real estate developers. Real estate speculation is a major element in the urban expansion process of the cities. In this sense, urban interventions are configured on common practices in the cities, being used in political speeches and economic development, hiding their true nature: the real estate overvaluation of certain locality. But it is responsible for urban growth, changing the form and content of elements that fall within the spatial relationships. Phenomena such as gentrification, social exclusion and socio-spatial or residential segregation, occurring over the control of land use. Goiania in this process was no different phenomena like these were, and are part of the urban history of the city. As an example there is the Region city Mendanha, this study object of study the region is the result of socio-spatial segregation, public and private urban interventions, real estate valuation and important socio-spatial transformations.